Fiber Bragg gratings - Kashyap, Raman (Optics and photonics., 2010)
Provides an overview of Fiber Bragg Gratings (FBGs), from fundamentals to applications Evaluates the advantages and disadvantages of particular applications, methods and techniques Contains new chapters on sensing, femtosecond laser writing of FBGs and poling of glass and optical fibers This fully revised, updated and expanded second edition covers the substantial advances in the manufacture and use of FBGs in the years since the publication of the pioneering first edition. It presents a comprehensive treatise on FBGs and addresses issues such as the merits of one solution over another; why particular fabrication methods are preferred; and what advantages a user may gain from certain techniques. Beginning with the principles of FBGs, the book progresses to discuss photosensitization of optical fibers, Bragg grating fabrication and theory, properties of gratings, specific applications, sensing technology, glass poling, advances in femtosecond laser writing of Bragg gratings and FBG measurement techniques. In addition to material on telecommunications usage of FBGs, application areas such as fiber lasers and sensors are addressed in greater detail. In addition to researchers, scientists, and graduate students, this book will be of interest to industrial practitioners in the field of fabrication of fiber optic materials and devices. Raman Kashyap, Canada Research Chair holder on Future Photonics Systems, and Professor at cole Polytechnique, University of Montral since 2003, has researched optical fibers and devices for over 30 years. He pioneered the fabrication of FBGs and applications in telecommunications and photonics. Provides an overview of Fiber Bragg Gratings (FBGs), from fundamentals to applications Evaluates the advantages and disadvantages of particular applications, methods and techniques Contains new chapters on sensing, femtosecond laser writing of FBGs and poling of glass and optical fibers.